Revenue Potential, Tax Space, and Tax Gap : A Comparative Analysis - Khwaja, Munawer Sultan; Iyer, Indira (World Bank, Washington, DC, 2014)
This paper contributes to the empirical literature on the key determinants of the revenue generating potential in 61 countries. The paper uses a broad set of data and econometric methods to conduct analyses that are of relevance to revenue potential. Earlier studies have not distinguished between the revenue potential based on economic fundamentals of countries and that based on what the legal framework prescribes. This study uses a dual approach to revenue potential to examine the issue. Two sets of variables are used, one related to the intrinsic economic structure and strength of countries that affect revenue potential and the other related to tax policy variables. Accordingly the analysis finds two sets of revenue potentials: one can be termed "revenue potential (economic)," and the other "revenue potential (legal)." The difference between the revenue potential (legal) and the actual revenue collected is commonly understood as the "tax gap." The difference between the revenue potential (economic) and the actual revenue collected can be termed the "tax space," the amount of revenue that a country can afford to collect, given its economic strength, not based on what the parliament has mandated. The results show that legally mandated revenue potentials in countries in Eastern Europe and Central Asia are often higher than the revenue potential based on what the country's economic fundamentals can afford. The paper also makes use of a tax effort index and finds that although many countries are performing close to the revenue potential (economic), it is more difficult to match up to the revenue potential (legal). The relationship between the revenue potential and the shadow economy, value added tax productivity, and some other determinants are examined to test whether some countries are taxing beyond their means.